2016
DOI: 10.1038/ncomms13607
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging with engineered physiology

Abstract: In vivo imaging techniques are powerful tools for evaluating biological systems. Relating image signals to precise molecular phenomena can be challenging, however, due to limitations of the existing optical, magnetic and radioactive imaging probe mechanisms. Here we demonstrate a concept for molecular imaging which bypasses the need for conventional imaging agents by perturbing the endogenous multimodal contrast provided by the vasculature. Variants of the calcitonin gene-related peptide artificially activate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…For example, it has recently been reported that changes in vascular flow in parenchymal arterioles can alter pyramidal neuron activity in cortical slices . And conversely, centrally released CGRP can also alter in vivo blood flow deep in the brain . It is intriguing to speculate that these mechanisms might allow communication between peripheral and central CGRP actions in migraine.…”
Section: Modulation In the Brain And Peripherymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has recently been reported that changes in vascular flow in parenchymal arterioles can alter pyramidal neuron activity in cortical slices . And conversely, centrally released CGRP can also alter in vivo blood flow deep in the brain . It is intriguing to speculate that these mechanisms might allow communication between peripheral and central CGRP actions in migraine.…”
Section: Modulation In the Brain And Peripherymentioning
confidence: 99%
“…33 And conversely, centrally released CGRP can also alter in vivo blood flow deep in the brain. 34 It is intriguing to speculate that these mechanisms might allow communication In this scenario, the neuropeptide from neuron 3 has enhanced the EPSP caused by the neurotransmitter from neuron 1. The nonmodulated EPSP from neuron 1 alone is shown as a solid line and the EPSP following stimulation of neurons 1 and 3 is shown as the dashed line.…”
Section: Modulation In the Brain And Peripherymentioning
confidence: 99%
“…Another recently introduced mechanism for biomolecular MRI involves peptides that act on smooth muscle cells to increase blood flow locally, resulting in blood oxygenation level dependent (BOLD) contrast [101] (Fig. 1g).…”
Section: Emerging Mechanisms Of Biomolecular Mri: Diffusion Hypermentioning
confidence: 99%
“…However, unlike most other amplified reporters, no external administration of contrast agents is required, and kinetics can be rapid, since the blood flow can increase and decrease on a second timescale in response to appropriate signals. Furthermore, CGRP can be engineered as a molecular sensor, for example by incorporating autoinhibitory domains that become cleaved by proteases [101]. …”
Section: Emerging Mechanisms Of Biomolecular Mri: Diffusion Hypermentioning
confidence: 99%
“…Pioneering examples include enzymes that alter the relaxivity of gadolinium chelates 39 , human iron storage and transport genes such as ferritin 40, 41 and transferrin 42 , and natural and engineered proteins with large numbers of chemically labile protons for chemical exchange saturation transfer (CEST) imaging 4348 . Recent developments have also included reporter genes causing accumulation of MRI-detectable compounds 49 , proteins interacting with hyperpolarized molecules 50, 51 , channels that alter the diffusion of water across cell membranes 52, 53 and vasodilators altering hemodynamic signals 54 . Several of these reporter genes are covered in detail in previous review articles 5557 .…”
Section: Main Textmentioning
confidence: 99%